Gene expression and DNA methylation changes in the hypothalamus and hippocampus of adult rats developmentally exposed to bisphenol A or ethinyl estradiol: a CLARITY-BPA consortium study. Issue 7 (3rd July 2018) - Cheong, Ana; Johnson, Sarah A.; Howald, Emily C.; Ellersieck, Mark R.; Camacho, Luísa; Lewis, Sherry M.; Vanlandingham, Michelle M.; Ying, Jun; Ho, Shuk-Mei; Rosenfeld, Cheryl S.
ABSTRACT: Bisphenol A (BPA), an endocrine disrupting chemical (EDC), is a ubiquitous pollutant. As part of the Consortium Linking Academic and Regulatory Insights on BPA Toxicity (CLARITY-BPA), we sought to determine whether exposure of Sprague-Dawley rats to 2, 500 μg/kg/day BPA (BPA) or 0.5 μg/kg/day ethinyl estradiol (EE) from gestational day 6 through postnatal day 21 induces behavior-relevant gene expression and DNA methylation changes in hippocampus and hypothalamus at adulthood. RNA and DNA were isolated from both regions. Expression of ten genes ( Dnmt1, Dnmt3a, Dnmt3b, Esr1, Esr2, Avp, Ar, Oxt, Otr, and Bdnf ) presumably altered by early-life BPA/EE exposure was examined. Three genes ( Bdnf, Dnmt3b, and Esr1) were studied for DNA methylation changes in their putative 5ʹ promoter regions. Molecular changes in hippocampus were correlated to prior Barnes maze performance, including sniffing correct holes, distance traveled, and velocity. Exposure to BPA and/or EE disrupted patterns of sexually dimorphic gene expression/promoter DNA methylation observed in hippocampus and hypothalamus of controls. In the hippocampus of female offspring, BPA exposure resulted in hypermethylation of the putative 5ʹ promoter region of Bdnf, while EE exposure induced hypomethylation. Bdnf methylation was weakly associated with Bdnf expression in hippocampi of female rats. Hippocampal Bdnf expression in females showed a weak negative association with sniffing correct hole in Barnes maze. Hippocampal expression of Avp, Esr2, Oxt, and Otr was strongly associated with velocity of control rats in Barnes maze. Findings suggest BPA exposure induced non-EE-like gene expression and epigenetic changes in adult rat hippocampi, a region involved in spatial navigation.